The physics companion - Fischer-Cripps, Anthony C. (Taylor & Francis, 2003)
"The Physics Companion presents a detailed and self contained yet concise account of the core subjects covered in an undergraduate physics degree. Individual topics are covered in unique one-page summaries, making for a friendly and informative resource. The perfect supplement to more traditional general physics texts. The Physics Companion can also be used as a stand-alone reference and is the ideal aid to revision."